Nightstick Fractures, Outcomes of Operative and Non-Operative Treatment - Ali, Mohammed; Clark, D I; Tambe, Amole (Acta medica (Hradec Kralove), 2019)
INTRODUCTION: A nightstick fracture is an isolated fracture of the ulnar shaft. Although operative and non-operative treatments have been commonly decided by the degree of displacement of the fracture, still there is a controversy specially in those moderately displaced. Herein we report our experience with nightstick fractures. OBJECTIVE: To evaluate operative and non-operative treatment of nightstick fracture. MATERIALS AND METHODS: We retrospectively reviewed the clinical notes, physiotherapy letters and radiographs of 52 patients with isolated ulnar shaft fractures. Outcome Measurements included radiographic healing, post-operative range of motion and complications. RESULTS: The study included 13 females and 39 males, with a mean age of 26 years [range, 18-93 years]. The mean Follow-up period was 32 months ranged from 12 to 54 months. Ten patients were treated non-operatively; forty-two patients had open reduction and internal fixation including six open fractures. The average wait for surgery was 2.5 days. Mobilisation was commenced immediately after the surgeries non-load bearing. 40 patients had no complications post-operatively with good outcome and average of four visits follow-up. In the non-operative group, five out ten failed and had a mean follow-up of nine visits. CONCLUSION: Satisfactory outcome is to be expected with open reduction and internal fixation. Fractures with less than 50% displacement should be treated on individual bases, considering; age, pre-morbid functional status, co-morbidities, compliance and associated injuries.
Keywords: výsledek terapie; Young Adult; Ulna Fractures; Comorbidity; Male; Immobilization; Postoperative Complications; retrospektivní studie; Fracture Fixation, Internal; ulnar shaft fracture; Fracture Healing; mladý dospělý; vnitřní fixace fraktury; imobilizace; non-operative management; radiografie; Adult; non-union; Age Factors; Aged; dospělí; mužské pohlaví; senioři; pooperační komplikace; komorbidita; Treatment Outcome; senioři nad 80 let; konzervativní terapie; lidé; ženské pohlaví; Humans; nightstick fracture; věkové faktory; Aged, 80 and over; fraktury ulny; Retrospective Studies; Conservative Treatment; Female; lidé středního věku; hojení fraktur; Radiography; Middle Aged